A zoomed-in view of participant 11 from Fig 8. - Mohammed Safayet Arefin (22683505) (2025)
Here, because of the expanded y axis, the lines from the fitted model can be seen. This shows the main effect of environment on eye visual angle (EVA): relative to Real targets, EVA was smaller for AR targets, and smaller for VR targets. The contrast coefficients (Fig 7) give these distances. x marks a_part = .79, the intercept for participant 11.